2020
DOI: 10.1039/d0nr04666c
|View full text |Cite
|
Sign up to set email alerts
|

Degradable self-adhesive epidermal sensors prepared from conductive nanocomposite hydrogel

Abstract: Conductive hydrogels based epidermal sensors are attracting enormous interest due to their great potential in soft robotics, electronic skins, bioelectronics and personalized healthcare monitoring. However, the conventional conductive hydrogels based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 57 publications
1
30
0
Order By: Relevance
“…Mussel, a classic example of wet surface adhesion in nature, achieves excellent adhesion by secreting special adhesive proteins containing high levels of catechol amino acid ( Yu et al, 2020 ). Several investigations have demonstrated that polydopamines, the mussel-inspired biomaterials with good biocompatibility and biodegradability ( Li et al, 2020 ), exhibited excellent adhesion properties on almost any surface ( Suneetha et al, 2019 ; Shao et al, 2020 ). For example, Jia et al reported on the use of polydopamine microcapsules in prolonging the retention time of pesticides on leaves ( Jia et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mussel, a classic example of wet surface adhesion in nature, achieves excellent adhesion by secreting special adhesive proteins containing high levels of catechol amino acid ( Yu et al, 2020 ). Several investigations have demonstrated that polydopamines, the mussel-inspired biomaterials with good biocompatibility and biodegradability ( Li et al, 2020 ), exhibited excellent adhesion properties on almost any surface ( Suneetha et al, 2019 ; Shao et al, 2020 ). For example, Jia et al reported on the use of polydopamine microcapsules in prolonging the retention time of pesticides on leaves ( Jia et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The volume resistivity (r) of the conductive path was measured by a four-probe method and calibrated using formula (2). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additive manufacturing technology has attracted increasing attention towards printed circuit boards (PCBs) and integrated circuits (ICs) because it provides enormous potential and opportunities for the production of diverse electronic devices such as multi-axial sensors, wearable electronic equipments and e-skins for robotics applications. [1][2][3] The conventional subtractive manufacturing has many drawbacks including complex process, long production cycle, and serious environmental pollution. 4,5 Inkjet printing or screen printing served as low cost, simple implementation and environmentally friendly technologies that can be utilized directly for conductive patterns.…”
Section: Introductionmentioning
confidence: 99%
“…To prepare the sensorized gelatin hydrogel (SGH), aqueous carbon black (CB) is added to the mix and allowed to homogenise. The addition of conductive elements to hydrogels and specific gelatin-based hydrogels has been explored previously [26], [27], [28], and is a widely used approach for developing inorganic strain and pressure sensors [29], [30], [31].…”
Section: A Hydrogel Preparationmentioning
confidence: 99%